Six new species of cernotina ross, 1938 (Trichoptera: Polycentropodidae) from Brazil - Silva, Patrik Barcelos e; Camargos, Lucas Marques de; Pes, A. M.; Salles, Frederico Falcaõ (Zootaxa, 2013)
Six new species of Cernotina Ross are described from two Brazilian states: Cernotina anhanguera sp. nov., Cernotina bispicata sp. nov., and Cernotina falcata sp. nov. from Goiás State (Cerrado biome) and Cernotina lanceolata sp. nov., Cernotina longispina sp. nov., and Cernotina sinuosa sp. nov. from Espírito Santo State (Atlantic Forest biome). In ad-dition, we report the first record of Cernotina spinigera Flint 1971 from Goiás State. Copyright © 2013 Magnolia Press.
Keywords: Anhanguera; Cernotina; Cernotina Spinigera; Lanceolata; Polycentropodidae; Trichoptera; Anatomy And Histology; Animals; Animals Dispersal; Classification; Insect; Physiology; Species Difference; Animals Distribution; Animal; Insects; Species Specificity